A Facile approach to NiCoO2 intimately standing on nitrogen doped graphene sheets by one-step hydrothermal synthesis for supercapacitors1. Issue 13 (7th April 2015) - Xu, Yazhou; Wei, Junchao; Tan, Licheng; Yu, Ji; Chen, Yiwang
<x xml:space="preserve">Abstract</x> Binary nickel cobaltite oxides intimately standing on nitrogen-doped reduced graphene sheets are prepared utilizing a one-step hydrothermal synthesis.